Analisis Faktor Keberlanjutan Pengelolaan Sampah di Tempat Pengolahan Sampah Terpadu (TPST) Kabupaten Sleman Menggunakan Pendekatan Multidimensional Scaling (MDS-RAPS) - Zahra Yulliandra; Mochammad Chaerul (Dampak, 2026)
ABSTRACT The permanent closure of the Piyungan Landfill due to overcapacity and the open-dumping system prompted the Sleman Regency Government to operate three Integrated Waste Treatment Facilities (TPST) based on Refuse-Derived Fuel (RDF), namely the Tamanmartani, Donokerto, and Sendangsari TPSTs. However, these three TPSTs still face challenges, including suboptimal processing capacity, the continued presence of residual waste, and their inability to fully contribute to achieving Sleman Regency’s waste management and reduction targets. This study aims to analyze the current conditions, sustainability factors, sustainability status, and waste management development strategies at the three TPSTs using the Multidimensional Scaling-Rapid Appraisal for Sustainability (MDS-RAPS) approach, which examines five aspects: operational technical aspects, institutional aspects, financing, regulations, and community participation. Data were collected through questionnaires administered to the public, TPST managers, and relevant agencies, and were subsequently analyzed using a SWOT analysis. The analysis results indicate that, in general, all three TPSTs are at a moderately sustainable level; however, the Tamanmartani TPST is less sustainable in the technical-operational aspect (48,92), and the Sendangsari TPST is less sustainable in the community participation aspect(46,41). The dominant factors in each aspect are: processing technology efficiency (technical-operational), the duties and responsibilities of the operators (institutional), the adequacy of TPST workers’ wages (financial), compliance with waste collection fee regulations (regulatory), and community efforts to maintain environmental cleanliness (community participation). The SWOT analysis places all three TPSTs in Quadrant I; therefore, the recommended sustainability strategy is an aggressive strategy (SO), which leverages internal strengths to optimize available opportunities to achieve sustainable waste management in Sleman Regency. Keyword: Integrated Waste Treatment Facility (TPST), Sustainability, MDS-RAPS, SWOT analysis, Waste management, Sleman Regency, Sustainability Strategy ABSTRAK Penutupan permanen TPA Piyungan akibat overcapacity dan sistem open dumping mendorong Pemerintah Kabupaten Sleman mengoperasikan tiga Tempat Pengolahan Sampah Terpadu (TPST) berbasis Refuse-Derived Fuel (RDF), yaitu TPST Tamanmartani, Donokerto, dan Sendangsari. Namun, ketiga TPST masih menghadapi kendala berupa kapasitas pengolahan yang belum optimal, masih adanya residu, serta belum maksimal dalam membantu tercapainya target penanganan dan pengurangan sampah Kabupaten Sleman. Penelitian ini bertujuan menganalisis kondisi eksisting, faktor keberlanjutan, status keberlanjutan, dan strategi pengembangan pengelolaan sampah pada ketiga TPST menggunakan pendekatan Multidimensional Scaling-Rapid Appraisal for Sustainability (MDS-RAPS) yang meninjau lima aspek yaitu teknis operasional, kelembagaan, pembiayaan, regulasi, dan partisipasi masyarakat. Data diperoleh melalui kuesioner kepada masyarakat, pengelola TPST, dan instansi terkait, kemudian dianalisis menggunakan SWOT. Hasil analisis menunjukkan bahwa secara umum ketiga TPST berada pada status cukup berkelanjutan, terkecuali TPST Tamanmartani pada aspek teknis operasional (48,92) memiliki status kurang berkelanjutan dan TPST Sendangsari para aspek partisipasi masyarakat (46,66) memiliki status kurang berkelanjutan, dengan faktor dominan pada masing-masing aspek yaitu efisiensi teknologi pengolahan (teknis operasional), tugas dan tanggung jawab pengelola (kelembagaan), kesesuaian gaji pekerja TPST (pembiayaan), kepatuhan terhadap peraturan retribusi sampah (regulasi), dan upaya masyarakat dalam menjaga kebersihan lingkungan (partisipasi masyarakat). Analisis SWOT menempatkan ketiga TPST pada Kuadran I, sehingga strategi keberlanjutan yang direkomendasikan adalah strategi agresif (SO) dengan memanfaatkan kekuatan internal untuk mengoptimalkan peluang yang tersedia guna mewujudkan pengelolaan sampah yang berkelanjutan di Kabupaten Sleman. Kata Kunci: Tempat Pengolahan Sampah Terpadu (TPST), Keberlanjutan, MDS-RAPS, analisis SWOT, Pengelolaan sampah, Kabupaten Sleman, Strategi Keberlanjutan